Development and Characterization of an HCMV Multi-Antigen Therapeutic Vaccine for Glioblastoma Using the UNITE Platform - Adhikari, Amit S.; Macauley, Juliete; Johnson, Yoshimi; Connolly, Mike; Coleman, Timothy; Heiland, Teri (Frontiers in Oncology, 2022)
Glioblastoma (GBM) is an aggressive form of brain cancer with a median survival of 15 months which has remained unchanged despite advances in the standard of care. GBM cells express human cytomegalovirus (HCMV) proteins, providing a unique opportunity for targeted therapy. We utilized our UNITE (UNiversal Intracellular Targeted Expression) platform to develop a multi-antigen DNA vaccine (ITI-1001) that codes for the HCMV proteins- pp65, gB and IE-1. The UNITE platform involves lysosomal targeting technology, fusing lysosome-associated membrane protein 1 (LAMP1) with target antigens. We demonstrate evidence of increased antigen presentation by both MHC-I and -II, delivering a robust antigen-specific CD4 and CD8 T cell response in addition to a strong humoral response. Using a syngeneic, orthotopic GBM mouse model, therapeutic treatment with the ITI-1001 vaccine resulted in 56% survival of tumor bearing mice. Investigation of the tumor microenvironment showed significant CD4 infiltration as well as enhanced Th1 and cytotoxic CD8 T activation. Regulatory T cells were also upregulated after ITI-1001vaccination. In addition, tumor burden negatively correlated with activated IFNCD4 T cells, reiterating the importance of CD4 activation in ITI-1001 efficacy and in identifying treatment responders and non-responders. Further characterization of these two groups showed high infiltration of CD3+, CD4+ and CD8+ T cells in responders compared to non- responders. Thus, we show that vaccination with HCMV antigens using the ITI-1001-UNITE platform generates strong cellular and humoral immune responses, triggering significant anti-tumor activity, leading to enhanced survival in a mouse model of GBM.